Temporal dynamics of forest fuels and effect of fire in cerro Nambiyugua, Chiapas, Mexico - Ruiz-Corzo, Roldan; Aryal, Deb Raj; Venegas-Sandoval, Andrea; Jerez-Ramírez, Deysi O.; Fernández-Zúñiga, Karla S.; Susana del Carmen; López-Herández, Juan Carlos; Peña-Alvarez, Beatriz; Velázquez-Sanabria, Carlos Alberto (Ecosistemas y Recursos Agropecuarios, 2022)
Forest fuel is one of the main carbon pools, but is also considered a factor involved in the occurrence and intensity of forest fires. The objective of this study was to analyze the temporal dynamics of forest fuel storage and the effect of fire in a pine (Pinus oocarpa Schiede) forest. The measurement of fresh and decomposed litter, and woody materials was carried out from 2010 to 2021 at four sites of a pine forest in the Cerro Nambiyugua, Villaflores, Chiapas, with the National Forest and Soil Inventory method. At each site, eight 30 x 30 cm2 quadrants were used to collect litter samples. To dry the samples, paper bags were used and placed in an oven at 70°C for 72 hours. The fallen woody material was sampled with the line intersection method. Fresh and decomposed litter load increased gradually over time. The highest litter loads were obtained in 2018 with 12.67 t ha-1. After the forest fire in 2019, the litter load decreased to 5.67 t ha-1, and by 2021 it increased to 8.65 t ha-1. The accumulation trend of fallen woody material varied according to the category of ignition hours. The results of this study have fundamental implications in the strategies and periodicity of forest fuel load management and carbon storage, since a greater frequency of forest fires is expected with climate change.